Warehouses and Warehouse Districts in Mid-American Cities - Eaton, Leonard (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1982)
In the late nineteenth century, the construction of warehouse districts became an important part of the building process in the North American city. These warehouse districts were the centres of activity for the wholesalers who were the key agents for the expansion of mercantile capitalism. The warehouses themselves were often structures of unusual architectural distinction. With the railroad station, the warehouse was ordinarily the true civic monument of the North American city. This article studies the process by which the wholesale district was formed.